MacJannet School children applauding Amelia Earhart during her visit to St. Cloud, ca. 1930 - Associated Press of Great Britain, Ltd. (Tufts Archival Research Center, 2005)
8x10; taken from MS024/007-095#014 - "MacJannet School." Donald MacJannet and Emory and Jean Foster are seen in the background of the photo.